Given that y=ln([2x-1/2x=1]^1/2) , show that dy/dx= (1/2x-1)-(1/2x+1)

y=ln([2x-1/2x=1]^1/2)- can be written as y= [0.5ln(2x-1)]-[0.5ln(2x+1)] due to laws of logs. Take first term -- (0.5ln(2x-1)) and substitute 2x-1 for u. so u=2x-1 and y=0.5lnu Now dy/du=1/2u and du/dx=2. to find dy/dx, times these 2 together - giving dy/dx=2/2u = 1/u = 1/2x-1 Doing the same method for the second term gives you that d/dx of 0.5ln(2x+1)is dy/dx= 1/2x+1 Therfore by subbing these back into the orignial equation,l the derivative of the enitre equation becomes dy/dx = (1/[2x-1])-(1/[2x+1])

Answered by Sam F. Maths tutor

9965 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

The velocity of a moving body is given by an equation v = 30 - 6t, where v - velocity in m/s, t - time in s. A) What is the acceleration a in m/s^2? B) Find the expression for the displacement s in terms of t given the initial displacement s(0)=10 m.


How do I solve quadratic equation by completing the square : X^2 - 4X = 5


By expressing cos(2x) in terms of cos(x) find the exact value of the integral of cos(2x)/cos^2(x) between the bounds pi/4 and pi/3.


Solve the following inequality and shade the region to which it applies on a graph. 10x(squared) < 64x - 24


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences